Surplus food recovery and donation in Italy: the upstream process. Issue 9 (26th August 2014) - Garrone, Paola; Melacini, Marco; Perego, Alessandro
Abstract : Purpose: – This paper offers quantitative evidence on how surplus food, i.e. safe food that is not sold to the intended customers, is generated and recovered within Italian manufacturing and retail firms. The purpose of this paper is to enlighten the process through which the food supply chain firms come to donate surplus food-to-food banks. Design/methodology/approach: – Surplus food and recoverability were defined as the key terms of the problem. In total, 12 exploratory case studies were conducted to segment the manufacturing and retail sectors, to assess recoverability in each segment, and to establish the protocols for descriptive case studies. A multiple case-study approach was used and 83 firms were investigated. Findings: – The primary source of surplus food is shown to result from products reaching the internal sell-by date, i.e. the date by which manufacturers and warehouses must supply perishable products. Donation to food banks is found to be a relevant management practice in the ambient and chilled manufacturing segments and at retail distribution centres, while frozen food companies and retail stores are found to rely nearly exclusively on waste disposal. Research limitations/implications: – The degree to which our findings are specific to Italy is an issue to investigate. Future research should target surplus food management in farming and food services, and assess the cost effectiveness of alternative management channels. Practical implications: – The paper highlights the changes required to increase the amount of food recovered by food banks. It also summarises the steps for establishing a structured procedure for managing surplus food within firms. Originality/value: – The paper offers quantitative evidence on a relatively untapped yet socially relevant topic, i.e. the upstream process of food recovery and donation.